Insulation assemblies for batteries, including fluoropolymers - Patents.com

JP2024518501A5Active Publication Date: 2025-04-14SOLVAY SPECIALTY POLYMERS ITALY SPA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023569814
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-12
Filing Date
2022-05-06
Publication Date
2025-04-14
Estimated Expiration
2042-05-06

AI Technical Summary

Technical Problem

Existing fluoropolymers used in electrochemical cell insulation assemblies, such as TFE/PPVE copolymers, suffer from low mechanical properties, reduced thermal stability, and high viscosity, leading to defects and corrosion during injection molding, which limits their effectiveness in manufacturing insulating components for secondary batteries.

Method used

A composition of TFE/PAVE fluoropolymers with specific molar ratios and melt flow rates is used, allowing for injection molding at lower temperatures and faster speeds, reducing weight loss and outgassing, while maintaining mechanical and chemical resistance.

Benefits of technology

The TFE/PAVE fluoropolymers enable defect-free, high-quality insulating assemblies with comparable mechanical and chemical properties to traditional TFE/PPVE polymers, extending equipment lifespan and improving manufacturing efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to an insulating assembly for an electrochemical cell comprising one or more fluoropolymers comprising: - 87 to 99 mol % of repeat units derived from tetrafluoroethylene (TFE); - 1 to 13 mol % of repeat units derived from perfluoromethyl vinyl ether (PMVE); - 0 to 3 mol % of repeat units derived from perfluoropropyl vinyl ether (PPVE); and having a melt flow rate (MFR) (measured at 372°C under a 5 kg load) of 40 to 300 g / 10 min.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to European Patent Application Publication No. 21173659.0, filed May 12, 2021, the entire contents of which are incorporated herein by reference for all purposes.

[0002] The present invention relates to an insulating assembly for use in the construction of electrochemical cells, particularly for use in secondary batteries, comprising certain selected copolymers of tetrafluoroethylene (TFE) and perfluoroalkylvinylether (PAVE), a method for producing such an insulating assembly via injection molding, and an electrochemical cell comprising such an insulating assembly. [Background technology]

[0003] As known to those skilled in the art, a battery contains one or more individual electrochemical cells that can convert chemical energy into electrical energy. Some batteries can only be used once, while others can be recharged by converting electrical energy into chemical energy that can be released again as electrical energy when the battery is used. These are called "rechargeable batteries" or "secondary batteries." Rechargeable batteries are gaining more attention in the industry, especially due to the current interest in electric engines.

[0004] Each electrochemical cell typically contains a number of "active" elements that are directly involved in the energy conversion process: a positive electrode, a negative electrode, a porous separator, and an electrolyte, which is typically a liquid, but may also be in gel or solid form. Commercial batteries typically pack one or more electrochemical cells into a container.

[0005] Besides the mentioned active elements, electrochemical cells also include other assembly parts that are not active per se, but are necessary and crucial to ensure the proper construction and performance of the cell. Each cell must in fact be electrically isolated from the other cells by a cell case, and the positive and negative terminals must also be available outside the cell case to allow the connection of the cells. In typical cell configurations, such as cylindrical or prismatic cells, this is achieved by using a cell cap that typically includes a safety vent to avoid bulging of the cell if gas forms inside. A sealing and insulating gasket is typically present around the cap or closure to seal the cell against electrolyte leakage and moisture ingress, and is in contact with the active elements of the cell, so the gasket must also be made of an electrically insulating material. Furthermore, insulating plates are typically present on both sides of the electrodes to prevent undesired short circuits, and necessarily the insulating plates must also be made of an electrically insulating material. Other insulating assemblies, such as electrode holders (also referred to as current collector holders), are typically present in many electrochemical cell configurations, as known to those skilled in the art. Configurations can vary, and in some cases the same components can perform more than one function, while in other cases more individual components can be used to perform a single function. All these insulating assemblies have in common that they are electrical insulators, essentially inert to the chemicals present in the electrochemical cell, yet do not directly participate in the electrochemical reactions that enable the cell to function to store and / or release energy.

[0006] All these assemblies are crucial for the life and safety of the cell, since the failure of even one single component can cause leakage or short circuit. In particular, the assemblies made of insulating materials are in direct contact with the solvents present in the electrodes and / or electrolyte materials, and are exposed to continuous temperature fluctuations during the life of the battery. Therefore, these insulating assemblies must be manufactured using materials that are not only electrically insulating, but also able to withstand elevated temperatures, temperature changes, and contact with solvents and aggressive chemicals. They must also be flexible enough to ensure sealing and separation even when pressure or mechanical stress is repeatedly applied for a long time.

[0007] For this reason, high performance plastic materials are typically preferred for most insulating assemblies in electrochemical cells, especially in cells for secondary batteries which must ensure a long service life even in harsh environments.

[0008] Among these insulating assemblies, one component that has particularly great importance in electrochemical cell construction is the so-called "gasket" or "sealing gasket."

[0009] A gasket is a seal typically placed around a battery cap to prevent electrolyte leakage and moisture from the air from entering the battery. The sealing gasket also provides electrical insulation to prevent the positive and negative electrodes from touching and causing a short circuit. To ensure the safety and life of the battery, the sealing and insulating functions of the sealing gasket (e.g., for automotive applications) must guarantee continuous use for 15 years or more. The sealing gasket material must have the resilience to maintain the effectiveness of the seal under adverse conditions, such as high temperatures and long-term stresses that can cause creep deformation, and must maintain these properties over the entire life of the battery.

[0010] Another important insulating assembly is the so-called "insulating plate", which is a plastic sheet used to prevent short circuits between two conductors. For example, there are typically two insulating plates in a cylindrical cell. The first plate is installed between the bottom of the jelly roll and the bottom of the can. The second plate is installed between the top of the jelly roll and the sealing gasket. As known to those skilled in the art, insulating plates are often included in many different battery cell configurations with the same function.

[0011] Electrode holders are typically used to keep the electrode plates in place and to prevent short circuits. As mentioned above, insulating assemblies for electrochemical cells must have good mechanical and chemical properties and maintain those properties over time. For this reason, fluoropolymers, especially perfluorinated polymers, have been used to form such insulating assemblies.

[0012] Polytetrafluoroethylene-based thermoplastic materials meet all the requirements for forming battery insulating assemblies. There is ample disclosure in the prior art of the use of copolymers of TFE and PAVE to form such insulating assemblies, in particular the use of TFE / perfluoropropyl vinyl ether (PPVE) copolymers, commercially known as PFA.

[0013] For example, WO 13115374 by Daikin describes a sealing material for use in insulating assemblies for batteries, the sealing material being based on a TFE / PPVE copolymer having an MFR of about 4 g / 10 min at 372° C.

[0014] Insulation assemblies for electrochemical cells can be manufactured from fluoropolymers using melt processing techniques such as compression molding and injection molding. Injection molding is particularly preferred because it allows the use of multi-cavity molds, thus allowing the preparation of several insulation assemblies in a single injection process.

[0015] As known to those skilled in the art of molding, thermoplastic materials for injection molding are preferably processable at relatively low temperatures due to both lower corrosion of equipment and molds and lower energy consumption. Preferred materials for injection molding should also have low viscosity at processing temperatures so that molds with many more cavities can be filled without error, and also be capable of being injected into the mold at high speeds without forming surface defects on the finished product.

[0016] On the other hand, it is known that the viscosity and melting point of TFE / PPVE copolymers (such as those used in the cited prior art) can be lowered by increasing the PPVE content, but it is also known that such copolymers with a high PPVE content are not suitable for the intended applications, since the low viscosity is accompanied by a decrease in mechanical properties and also a decrease in thermal stability.

[0017] Thermal stability is not only relevant for the stability of the polymer itself, but also for injection molding of fluoropolymers, since weight loss is accompanied by the loss of various compounds, such as hydrogen fluoride (HF) in gas form, which is the main cause of corrosion for the expensive equipment typically used for injection molding, so that materials that lose weight when heated will also cause higher corrosion and, as a result, shorter life for the mold. Weight loss can also be related to gas evolution, which can cause the formation of defects such as bubbles in the molded part.

[0018] Therefore, there remains a need for insulating assemblies for electrochemical cells obtained from fluoropolymer compositions that meet all the requirements of known polymers such as mechanical stability, chemical resistance, insulating performance, sealing ability, etc., but can be injection molded at lower temperatures and are also more thermally stable during molding. Summary of the Invention

[0019] In one aspect, the present invention provides an insulating assembly for an electrochemical cell comprising one or more fluoropolymers, the fluoropolymer comprising: - 87 to 99 mol % of repeat units derived from tetrafluoroethylene (TFE), - 1 to 13 mol % of repeat units derived from perfluoromethylvinylether (PMVE), - 0 to 3 mol % of repeating units derived from perfluoropropyl vinyl ether (PPVE) and having a melt flow rate (MFR) of 40 to 300 g / 10 min (measured at 372° C. under a 5 kg load).

[0020] In another aspect, the present invention relates to a method of manufacturing an insulating assembly for an electrochemical cell, comprising forming said insulating assembly via injection molding of a thermoplastic polymer composition, said composition comprising one or more fluoropolymers as defined above.

[0021] In a further aspect, the present invention relates to a secondary battery preferably including an insulating assembly such as a sealing gasket, an insulating plate or an electrode holder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] For the purposes of this description, the term "insulating assembly" in reference to an electrochemical cell refers to all solid components of the electrochemical cell that are not involved in the electrochemical reaction (i.e., electrodes, electrolytes and separators) and that do not conduct electricity (i.e., excluding connectors, wiring, etc.). These are, for example, sealing gaskets, insulators, seals, electrode holders (also called current collector holders), insulating cases, insulating cells, etc. The electrochemical cell is typically a cell for a battery, preferably a secondary battery cell, more preferably a lithium battery cell. The insulating assembly is preferably a sealing gasket, an insulating plate and / or an electrode holder.

[0023] All percentages by mole or repeat units refer to the total amount of repeat units present in the polymer.

[0024] As mentioned above, the present invention relates to insulating assemblies for electrochemical cells, typically battery cells, where such assemblies include one or more selected TFE / PAVE fluoropolymers.

[0025] The TFE / PAVE fluoropolymers selected for the present invention contain 1 to 13 mol %, preferably 1 to 10 mol %, more preferably 2 to 8 mol %, and even more preferably 3 to 7 mol % of repeat units derived from perfluoromethylvinylether (PMVE).

[0026] The TFE / PAVE fluoropolymers selected for the present invention may also contain 0-3 mol %, preferably 0-2.5 mol %, more preferably 0-2 mol %, and even more preferably 0.1-1.5 mol % of repeat units derived from perfluoropropyl vinyl ether (PPVE).

[0027] Generally, the molar amount of repeat units derived from PPVE (if present at all) is less than the molar amount of repeat units derived from PMVE, i.e., the molar ratio between repeat units derived from PPVE and repeat units derived from PMVE (PPVE / PMVE) is less than 1, preferably less than 0.5, more preferably less than 0.3, and most preferably less than 0.2.

[0028] Optionally, the TFE / PAVE copolymer for use in the present invention contains up to 6% of perfluoro(2,2-dimethyl-1,3-dioxole) of formula (20A), perfluoro(1,3-dioxole) of formula (21A), and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxole of formula (26A): [ka] The monomer may include repeat units derived from a cyclic monomer selected from:

[0029] When present, such cyclic monomers are present preferably in an amount of 0.1 to 5 mol %, more preferably 0.1 to 4 mol %, and even more preferably 0.1 to 3 mol %.

[0030] The TFE / PAVE fluoropolymer selected for the present invention contains repeat units derived from TFE in an amount of 87-99 mol %. Other repeat units than those derived from TFE, PAVE and the above-mentioned cyclic monomers are preferably absent, but if present, are preferably fully fluorinated and preferably less than 2 mol % based on the total amount of repeat units of the fluoropolymer.

[0031] End chains, impurities, defects and small amounts of other comonomers (the latter generally in amounts not exceeding 0.5%, preferably not exceeding 0.1%, based on the total molar amount of repeat units of the polymer) may be present without them substantially affecting the properties of the TFE / PAVE copolymer.

[0032] The TFE / PAVE fluoropolymers selected for the present invention are further characterized by having a melt flow rate (MFR) of 40-300, preferably 50-200, more preferably 60-160, and even more preferably 70-130 g / 10 min (measured at 372° C. under a 5 kg load).

[0033] The TFE / PAVE fluoropolymers selected for the present invention preferably have a melting point T measured according to ASTM D3418 comprised between 260°C and 310°C, preferably between 270°C and 305°C, more preferably between 275°C and 300°C. m It can be further characterized as:

[0034] The insulating assembly of the present invention is preferably made of a composition, preferably a thermoplastic polymer composition, in which the above selected TFE / PAVE fluoropolymer constitutes at least 80% by weight, preferably at least 90% by weight, more preferably at least 95% by weight, and most preferably at least 99% by weight of said insulating assembly.

[0035] Additional optional ingredients that may be added to the compositions used to manufacture the assemblies of the present invention are conventional additives such as stabilizing additives, mold release agents, plasticizers, lubricants, heat stabilizers, light stabilizers, antioxidants, adhesion promoters, fillers, pigments and others, preferably present in amounts less than 10% by weight of the composition.

[0036] If present, the fillers may be selected from inorganic fillers such as, for example, talc, mica, kaolin, calcium carbonate, calcium silicate, magnesium carbonate, graphite, carbon black, and the like.

[0037] The applicant has unexpectedly found that when insulating assemblies containing the above selected TFE / PAVE fluoropolymers are produced, production is possible through injection molding at lower temperatures and higher injection speeds than using the prior art TFE / PPVE fluoropolymers, which allows the use of multi-cavity molds, which is a particularly efficient method for producing such insulating assemblies. The use of the selected TFE / PAVE polymers of the present invention is associated with reduced weight loss and the resulting reduced generation of outgassing species such as HF during molding, which also leads to a longer life for the mold and fewer defects in the molded parts. The insulating assemblies of the present invention have comparable mechanical properties, chemical resistance and long-term stability compared to similar assemblies obtained using the prior art TFE / PPVE polymers. With regard to experimental data supporting the benefits provided by the present invention, the following examples are referred to.

[0038] Method for manufacturing an article The present invention also relates to a method of manufacturing an insulating assembly for an electrochemical cell, comprising forming an insulating assembly for use in an electrochemical cell via injection molding of a thermoplastic polymer composition, said composition comprising one or more selected TFE / PAVE fluoropolymers as described above.

[0039] In the method of the present invention, the mold is preferably a multi-cavity mold, more preferably a multi-cavity mold having at least four cavities, each cavity allowing for the molding of a separate insulating assembly. The low viscosity of the composition allows for rapid filling of multiple cavities efficiently under mild conditions of temperature and pressure, producing individual molded parts with smooth surfaces and free of defects.

[0040] Alternatively, but less preferably, the insulating assemblies of the present invention can be manufactured by other melt processing techniques different from compression molding or injection molding.

[0041] The injection molding process generally involves forcing a molten thermoplastic composition into a mold cavity using a ram or screw-type plunger; within the mold cavity, the composition solidifies to a shape that follows the contours of the mold, which can be a single-cavity or a multi-cavity mold.

[0042] As mentioned above, the injection molding process is preferably carried out using a thermoplastic composition comprising at least 80% by weight, preferably at least 90% by weight, more preferably at least 95% by weight, and most preferably at least 99% by weight of one or more of the selected TFE / PAVE fluoropolymers described above.

[0043] The injection molding process described herein is particularly suitable for the manufacture of insulating assemblies such as sealing gaskets and insulating plates, collector holders, etc. Typical shapes for the insulating assemblies of the present invention may vary depending on the geometry of the electrochemical cell. Exemplary shapes are, for example, flat parts (rectangular or disk shaped), disks, plates, o-rings, rods, etc., having a thickness of 0.2 to 1 mm.

[0044] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements of this application to the extent that a term may be unclear, this statement shall control.

[0045] The invention will now be described in more detail with reference to the following examples, the purposes of which are merely illustrative and are not intended to limit the scope of the invention. EXAMPLES

[0046] Test Method MFR: (Melt Flow Rate) is measured according to ASTM 1238 at 372°C under a piston load of 5 kg and is expressed as g / 10 min.

[0047] TGA: Weight loss tests were performed according to ISO 11358 using a TGA5500 instrument by TA.

[0048] Melting point determination Melting point T m was measured as the second melting temperature by DSC according to the ASTM D 3418 standard. The procedure was as follows: the polymer samples were melted by heating them from 10°C to 400°C with a temperature ramp of 10°C / min. The samples were then held at 400°C for 5 minutes and then the temperature was reduced from 400°C to 10°C with a ramp of 10°C / min to allow recrystallization. The polymer was then held at 10°C for 10 minutes and then heated again to 400°C with a temperature ramp of 10°C / min. The melting point was measured as the temperature of melting during this second ramp.

[0049] C-Set (Compression Set): Compression set values ​​were measured according to ASTM 395B. Samples were obtained from injection molded disks with an outer diameter of 120 mm and a thickness of 2 mm, prepared by injection molding according to the procedure described below. From these larger disks, smaller disk-shaped samples with a diameter of 13 mm and a thickness of 2 mm were cut. These smaller disks were subjected to a compression test. In the compression test, the samples were compressed along their original thickness of 2 mm, which was compressed down to 1 mm. The samples were kept under compression in an oven at 70° C. for 120 hours. After this time, the samples were removed from the oven, the compression was removed, and the thickness of the samples was measured after 30 minutes of room temperature conditioning. The C-Set values ​​were calculated according to the following formula: C-Permanent set (%)=[(t0-t i ) / t0-t s )] x 100 t o = the original thickness of the specimen (approximately 2 mm in this case) t s = target compressed thickness of the specimen (1mm in this case) t i = final thickness of specimen after room conditioning

[0050] Tensile properties: Yield stress was measured (in MPa) at 23° C. at 1% offset on molded plaques according to ASTM D3307. Test polymers in the form of pellets were subjected to melt compression molding at 360° C. in a vertical press for the production of plaques with a thickness of about 1.2 mm.

[0051] Dielectric Properties: Dielectric strength according to ASTM D149 and CTI (Comparative Tracking Index) according to ASTM D3638 were obtained on the same molded plaques used to measure the tensile properties.

[0052] Capillary test (sharkskin detection): carried out according to ASTM D 3835. The test was carried out on a capillary rheometer device (Rheograph 2003) using L / D=10 and D=1 and 0.54 mm. The molten material was extruded through a capillary and the surface of the extrudate was evaluated for its smoothness / roughness. This test was used to evaluate what was the maximum shear rate at which the material could be extruded (at a given T) without exhibiting surface roughness. The formation of surface roughness (sharkskin) is immediately evident to one skilled in the art of performing the capillary test by simple tactile inspection of the sample.

[0053] Materials used: Polymer P1 (according to the invention) - T of 281 ° C. m and a TFE / PPVE / PMVE copolymer containing 4.75 mol % PPMVE, 0.39 mol % PPVE and 94.86 mol % TFE, having an MFR at 372° C.-5 kg ​​of 88 g / 10 min.

[0054] Polymer P2 (comparison) - T of 308°C m and a 372° C.-5 kg ​​MFR of 13.3 g / 10 min.

[0055] Preparation of polymer P1 In a 22 liter AISI 316 steel vertical reactor equipped with an agitator operating at 400 rpm, the following ingredients were added after vacuum application: - 13.9lt demineralised water, - 85 g of perfluoropropyl vinyl ether (PPVE), - 128 g of a microemulsion prepared according to US Pat. No. 4,864,006 by mixing 39.7 g of one ionic perfluoropolyether with ammonium carboxylate end groups, 23 g of one perfluoropolyether with neutral end groups and 65.3 g of water. were introduced in order.

[0056] Once all the raw materials had been added, the reactor was heated up to 75°C and 0.15 bar of ethane and 3.7 bar of perfluoromethylvinylether (PMVE) were fed. A gaseous TFE / PMVE mixture in a molar ratio of 21 was then added by a compressor until a pressure of 21 absolute bar was reached. 118 ml of ammonium persulfate solution 0.044M was fed by a metering pump, thus starting the polymerization. The polymerization pressure was kept constant by feeding the monomer mixture and an additional amount of 8.6 g of ethane was added when a conversion of 20% was reached. After a total of 8715 g of the above mixture had been fed, the monomer mixture feed was interrupted, the stirring was stopped and the pressure was allowed to drop until it reached 7.5 absolute bar. The reactor was then cooled at room temperature and the emulsion was discharged and coagulated with a 65% solution of nitric acid. The polymer was washed with water, dried in an oven at 220° C., and then pelletized using a Coperion twin screw extruder 48D at an extrusion temperature of about 302° C. The nominal polymer composition was 4.75 mol % PMVE, 0.39 mol % PPVE, and 94.86 mol % TFE. The MFR was 88 g / 10 min, and the melting point was 281° C.

[0057] Injection molding of polymer P1 and polymer P2: Polymer P1 and polymer P2 were used to prepare disks with a diameter of 120 mm and a thickness of 2 mm by injection molding. The molding was carried out on an injection molding machine Negri-Bossi (NB100) with a barrel diameter of 30 mm. The disks obtained by injection molding were used for the C-set measurement as described above.

[0058] The molding conditions were optimized for both polymers P1 and P2: polymer P1 (according to the invention) was processed on an injection molding machine with C1 / C2 / C3 / C4 cylinder temperatures of 315 / 320 / 325 / 330° C., a nozzle temperature of 330° C. and a pressure (holding pressure) of up to 432 bar, while polymer P2 (comparative) was processed on an injection molding machine with C1 / C2 / C3 / C4 cylinder temperatures of 370 / 375 / 380 / 385° C., a nozzle temperature of 385° C. and a pressure (holding pressure) of up to 520 bar. Both molding operations required a cycle time of 65 seconds.

[0059] Both resulting discs were completely flat and without cracks or defects.This molding example shows how polymer P1 can be injection molded at lower temperatures and pressures than polymer P2.

[0060] Yield stress measurement The yield stress was measured on the molded plaques obtained as described above. The results obtained show that the samples of both polymers P1 and P2 have the same yield stress of about 12.5 MPa.

[0061] Compression set (C-set) measurement C-set was measured for both Polymer 1 and P2 samples prepared from molded disks as described above. The results showed that both samples had the same C-set of about 73%. The specimens after compression showed no defects or cracks.

[0062] Measurement of dielectric properties The dielectric strength and CTI were measured on the same molded plaques used for the measurement of the mechanical properties. The results obtained show that both polymers P1 and P2 have the same dielectric strength of about 32 KV / mm and a CTI of more than 600 V.

[0063] Capillary Test Both polymers P1 and P2 were subjected to a capillary test. The molten polymer was injected into the capillary of the instrument and extruded through it at various temperatures. The surface of the extruded material was evaluated as being smooth (passed) and rough (failed). The maximum shear rate at which the polymer exhibited a smooth surface at each temperature was recorded as the "sharkskin onset shear rate". The results are shown in Table 1.

[0064] [Table 1]

[0065] The results show how polymer P1 selected according to the invention can be injection molded at much higher speeds than polymer P2, without the risk of forming surface defects.

[0066] Measurement of weight loss Weight loss was measured on a TGA5500 instrument by TA on a 0.030 g sample. Two weight loss tests were performed. In the first test, the polymer sample was heated from room temperature to 380° C. at a temperature ramp of 10° C. per minute (dynamic heating test).

[0067] In the second test, the polymer samples were heated with the same ramp to their molding temperature (330° C. for P1 and 380° C. for P2) and the temperature was maintained for 4 hours (isothermal test). The weight loss data are reported in Table 2 below.

[0068] [Table 2]

[0069] The weight loss data shows how the sample of polymer P1 exhibits a reduced weight loss after dynamic heating up to 380°C. This implies a reduced generation of decomposition products such as HF gas during molding and thus a longer service life for the equipment and a reduced number of defects (e.g., bubbles) in the molded parts. Of note, in practical applications, the molding temperature of polymer P1 is much lower than that of P2, which implies an even more pronounced reduction in the generation of decomposition products as shown by the isothermal weight loss test.

[0070] Preparation of insulating assemblies for electrochemical cells Preparation example of insulating plate Polymer P1 was processed in an injection molding machine. The melt was injected into a multi-cavity mold with four cavities in the shape of a disk with a diameter of 8 mm and a thickness of 0.5 mm. The rings were all well formed, smooth and did not contain cracks or defects. The disks were then used as insulating plates for cylindrical Li-cells.

[0071] In general, the data show how the use of selected polymers of the present invention to manufacture insulating assemblies for batteries allows these parts to be efficiently manufactured via injection molding, using lower molding temperatures, faster injection molding processes (as the molten polymer can be subjected to higher shear rates) and recording lower weight loss during molding (corresponding to lower levels of corrosive gas emissions) compared to the common PFA polymers used in the art for the same applications. Surprisingly, the resulting parts have mechanical and electrical properties that match those of conventionally used PFA polymers.

Claims

1. 1. An insulation assembly for an electrochemical cell comprising one or more fluoropolymers, said fluoropolymers comprising: - 87 to 99 mol % of repeat units derived from tetrafluoroethylene (TFE), - 1 to 13 mol % of repeat units derived from perfluoromethylvinyl ether (PMVE), - 0 to 3 mol % of repeat units derived from perfluoropropyl vinyl ether (PPVE) and having a melt flow rate (MFR) of 40 to 300 g / 10 min (measured at 372° C. under a 5 kg load).

2. The one or more fluoropolymers are - 1 to 10 mol %, preferably 2 to 8 mol %, more preferably 3 to 7 mol % of repeat units derived from PMVE, - 0 to 3 mol %, preferably 0 to 2.5 mol %, more preferably 0 to 2 mol %, even more preferably 0.1 to 1.5 mol % of repeat units derived from PPVE 10. The insulation assembly of claim 1, comprising:

3. 2. The insulating assembly of claim 1, wherein the one or more fluoropolymers have a molar ratio between repeating units derived from PPVE and repeating units derived from PMVE (PPVE / PMVE) that is less than 1, preferably less than 0.5, more preferably less than 0.3, and most preferably less than 0.

2.

4. The one or more fluoropolymers have a melting temperature T m 2. The insulation assembly of claim 1, comprising:

5. 2. An insulating assembly according to claim 1, wherein the one or more fluoropolymers have a MFR (measured at 372° C. under a 5 kg load) of 50 to 200, preferably 60 to 160, more preferably 70 to 130 g / 10 min.

6. 2. The insulating assembly of claim 1, wherein the one or more fluoropolymers constitute at least 80% by weight of the insulating assembly, preferably at least 90% by weight, more preferably at least 95% by weight, and most preferably at least 99% by weight.

7. 2. An insulating assembly according to claim 1, wherein the electrochemical cells are battery cells, preferably secondary battery cells, more preferably lithium battery cells.

8. 10. The insulation assembly of claim 1, which is an injection molded insulation assembly.

9. 10. The insulating assembly of claim 1, which is a sealing gasket, an insulating plate or an electrode holder.

10. A method for manufacturing an insulating assembly for an electrochemical cell according to any one of claims 1 to 9, comprising forming said insulating assembly via injection moulding of a thermoplastic polymer composition, said thermoplastic polymer composition comprising: - 87 to 99 mol % of repeat units derived from tetrafluoroethylene (TFE), - 1 to 13 mol % of repeat units derived from perfluoromethylvinyl ether (PMVE), - 0 to 3 mol % of repeat units derived from perfluoropropyl vinyl ether (PPVE) and one or more fluoropolymers having a melt flow rate (MFR) of 40 to 300 g / 10 min (measured at 372° C. under a 5 kg load).

11. 11. The method of manufacturing an insulation assembly for an electrochemical cell according to claim 10, wherein the mold is a multi-cavity mold including at least four cavities, each cavity allowing for molding an individual insulation assembly.

12. 11. The method for manufacturing an insulating assembly for an electrochemical cell according to claim 10, wherein said thermoplastic polymer composition comprises at least 80% by weight, preferably at least 90% by weight, more preferably at least 95% by weight, and most preferably at least 99% by weight of said one or more fluoropolymers.

13. A secondary battery comprising at least one insulating assembly according to any one of the preceding claims.

14. The secondary battery according to claim 13 , wherein the at least one insulating assembly is a sealing gasket, an insulating plate and / or an electrode holder.

15. Use of a thermoplastic polymer composition comprising one or more fluoropolymers for producing insulating assemblies for use in electrochemical cells, preferably for producing sealing gaskets, insulating plates and / or electrode holders for secondary batteries, said fluoropolymers being - 87 to 99 mol % of repeat units derived from tetrafluoroethylene (TFE), - 1 to 13 mol % of repeat units derived from perfluoromethylvinyl ether (PMVE), - 0 to 3 mol % of repeat units derived from perfluoropropyl vinyl ether (PPVE) and having a melt flow rate (MFR) of 40 to 300 g / 10 min (measured at 372° C. under a load of 5 kg).